Analisis Perbandingan Kapasitas Lentur Balok Komposit Berdasarkan SNI 1729:2015 dan SNI 1729:2020 - Ahmad Sumantri; Ainil Mardhiyah; Nova Juliana (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Composite steel-concrete structures are widely applied in modern construction due to their material efficiency, high strength-to-weight ratio, and reliable structural performance. As design demand evolve, the Indonesian National Standard (SNI) continues to be updated to enhance safety and consistency in structural design. One significant revision occurred in SNI 1729:2020, which replaced SNI 1729:2015 and introduced changes in material strength provisions, strength-reduction factors, and flexural capacity calculations for composite members. However, quantitative studies examining the impact of these updates remain limited. This study aims to analyze and compare the flexural capacity of composite beams based on manual calculations following SNI 1729:2015 and SNI 1729:2020. Several types of steel girders with variations in span length and slab thickness were evaluated. The results indicate a very high level of equivalence between the nominal and factored flexural capacities obtained from both standards. All girder types produced identical values, demonstrating that no difference exists in the level of conservatism in estimating the flexural capacity of composite elements. Nevertheless, the use of SNI 1729:2020 is recommended due to its improved structure, alignment with the international standard ASIC 360-16, and harmonization with other updated SNI provisions, which collectively enhance the reliability of steel structural design in Indonesia